Frederick Lygon, Earl of Beauchamp, papers - Lygon, Frederick, Earl Beauchamp, 1830-1891.
Selections relating to the Corbin family of Virginia.
Photostats of originals at Madresfield Court (Great Malvern, Worcestershire, England).
Great Britain: Madresfield Court, Great Malvern, Worcestershire
British public official.
Finding aid available in the Library of Congress Manuscript Reading Room.
Keywords: Corbin family; Virginia -- Social life and customs; Public officials -- Great Britain